A robust and unique iron(ii) mosaic-like MOF. Issue 44 (10th May 2018) - Fernandez-Bartolome, Estefania; Santos, José; Khodabakhshi, Saeed; McCormick, Laura J.; Teat, Simon J.; de Pipaon, Cristina Saenz; Galan-Mascarós, Jose R.; Martín, Nazario; Sanchez Costa, Jose
Abstract : A novel Fe(ii ) MOF is reported to show an unprecedented 1D chain with a perfect linearity. Moreover, this structure expands to a third dimension to form a very robust MOF. The structure displays an amazing resemblance to a 14th century mosaic found in the Alhambra Palace in Granada. Abstract : A novel extended triazole-based ligand (PM-Tria ) has been synthesized and an unprecedented MOF 3D has serendipitously been formed by assembling iron(ii ), PM-Tria ligand and fluoride anions. This MOF contains a perfectly linear one-dimensional Fe(ii )–F n bridging chain that shows an antiferromagnetic behaviour. Furthermore, the structure is compared with a 14th century mosaic found in the Alhambra Palace in Granada showing a surprising symmetry resemblance.